Effect of reflow soldering process on metallurgical bonding between Sn3.5Ag solder and ENIG substrates - Muhammad N.A.; Bais B.H.; Ahmad I.; Isnin A. (2023)
Reflow soldering process is one of the important steps in the manufacturing process for ball grid arrays. The purpose of this study is to observe the metallurgical bonding between Sn3.5Ag solder ball and electroless nickel immersion gold (ENIG) substrates after reflow soldering process. The reflow soldering process was performed at peak temperatures T peak of 246 and 251C for 50 s by the rapid thermal processing system. Visual micrographs of these solder joints were performed in order to support the metallurgical bonding of Sn3.5Ag solder ball and ENIG substrate after the reflow soldering process. The formation of Ni 3Sn 4 intermetallic compounds (IMCs) at the Sn3.5Ag solder/Ni interface was dependent and continuous with one another compared to the initial IMC formation at Tpeak of ?246C. It was also found that the initial IMCs thickness of Sn3.5Ag solder/Ni interface was lower and thinner at Tpeak of y251uC during the reflow soldering process. As a conclusion, the metallurgical bonding between Sn3?5Ag solder/ENIG substrate was formed better at T peak of ?251C during the reflow soldering process using the rapid thermal processing system. W. S. Maney & Son Ltd. 2011.